Our Four Years of Paediatric Sepsis Treatment with Hemoadsorption, Albumin and Heparin: Let's Give it a Chance in Multifactorial Pathological Conditions - Leonardo, Milella; Fabiana, Cito; Pasquale, Raimondo; Teresa, Ficarella Maria; Paola, Moliterni; Michele, Sisto; Luigia, Lasorella Maria; Nadia, Lombardi; Milena, Maldera; Gerolmina, Calabrese (New Frontiers in Medicine and Medical Research Vol. 14, 2021)
Extracorporeal blood purification therapies are increasingly applied in the field of intensive care medicine. These techniques are applied to a relevant number of clinical situations as Sepsis, Trauma, burns, Influenza, surgery, Pancreatitis, ARDS, Life support, Liver failure. Compared to filtration-based methods mainly used for renal replacement therapy, newest adsorptive approaches have shown to specifically target the inflammatory cascade by the effective removal of relevant mediators. In the neonatal and pediatric setting however, the application of these methods brings with it various challenges but also profound technical difficulties. Recently, a promising extracorporeal device for cytokine adsorption (Cytosorb) has been introduced, however data for its application in critically ill pediatric patients remains sparse [1]. The lack of data and procedure protocols led us to take some aprioristic diagnostic and speculative decisions only from a scientific point of view: “in primis” when we decided for the first time in a pediatric patient to use this "Cytosorb Absorber", a device not registered and delivered for toddlers; second when it was clear that we could extend its use to not conventional disease therapeutic strategies; third when we decided to give to “Cytosorb” use the appellation and indication of “rescue treatment”. These results are interesting for the scientific community, but further research is needed.